Spatial and Temporal Distribution of the Multi-element Signatures of the Estuarine Non-indigenous Bivalve Ruditapes philippinarum - Vieira, Soraia (2022)
Filter-feeder bivalves such as non-indigenous Ruditapes philippinarum absorb and accumulate metals, resulting in multi-element profiles. The goal of this study was to analyse spatial and temporal distributions of the multi-element signatures in R. philippinarum populations of the Tagus and Sado estuaries (SW coast, Portugal). The clam and sediment samples were collected at three sampling sites in each estuary, on three sampling occasions, and the analysis were done by ICP-MS (inductively coupled plasma mass spectrometry). The chemical elements were categorized according to estuarine geomorphology sources (Se, Co, Ni and Cu), elements with function in metabolic processes of the clams (Mn, Fe, Zn and Cr) and elements derived from the anthropogenic inputs (As, Pb and Cd). Zinc, Co, Ni and Pb were the main contributors for the chemical signatures of Tagus estuary populations, whilst for the Sado estuary populations were Cu, Fe, Cr, As and Cd. They were representative of all elemental categories and proved to be spatial and temporal habitat discriminators of bivalves’ estuarine populations. The multi-element signatures of R. philippinarum as a natural tag derived from the physical and chemical conditions of its habitat is a potential rapid tool to use in ecological monitoring and habitat assessment.